Dengue in pregnancy, maternal and fetal outcome: a case series managed at a Zonal Hospital - Singh, Tina; Singh, S. M.; Paprikar, M. M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Dengue is a vector borne disease with various grades of severity. Pregnancy is a high-risk group and is prone for complications of dengue haemorrhagic fever. The aim of this study was to evaluate the clinical profile of pregnant patients with dengue and to assess the maternal and fetal outcomes of dengue in pregnancy. Methods: All pregnant patients reporting to the hospital with fever and serologically confirmed dengue infection were included in the study. Clinical and laboratory data of patients were collected. The cases were followed up till their delivery to monitor the effect of dengue. An account of the mode of delivery in these patients was made. The neonates were evaluated and followed up till 6 weeks of life. Results: A total 100% patients reported with fever and serologically confirmed dengue infection. 15% had severe thrombocytopenia requiring platelet transfusion. 31% required ICU care and 15% needed mechanical respiratory support due to severe complications of dengue. NICU admission rate was 30% but there was no major neonatal complication or vertical transmission noted. A high index of suspicion should be maintained by the clinician with an aim to identify infection early, start supportive treatment and evaluate for complications. In-patient care should be provided for feto-maternal monitoring. Conclusions: The progression of dengue infection in pregnancy was rapid leading to major complications. Close materno-fetal monitoring and timely obstetric care are essential to ensure a favorable pregnancy outcome